The Effectiveness of Mini Soccer Games in Increasing Children's Physical Activity - Rizky, Elfera; Noviardila, Iska (The Future of Education Journal, 2026)
This study aimed to determine the effectiveness of mini soccer games in increasing children’s physical activity. The low level of children’s physical activity has become one of the problems in physical education learning; therefore, an enjoyable learning model is needed to encourage children to be more active during the learning process. This study employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The research subjects consisted of 28 children aged 10–12 years selected through purposive sampling. The research instruments included the Physical Activity Questionnaire for Children (PAQ-C) and a physical activity observation sheet. The mini soccer game intervention was conducted for one month with a frequency of two sessions per week. Data were analyzed using descriptive statistics and a paired sample t-test with a significance level of 0.05. The results showed a significant increase in children’s physical activity after the implementation of the mini soccer game intervention, with a significance value of p < 0.05. The improvement in physical activity was indicated by increased movement intensity, active participation, and children’s enthusiasm during learning activities. Based on these findings, it can be concluded that mini soccer games are effective in increasing children’s physical activity and can be used as an alternative learning model in elementary school physical education.